2022
DOI: 10.1017/jfm.2022.78
|View full text |Cite
|
Sign up to set email alerts
|

Torque scaling at primary and secondary bifurcations in a Taylor–Couette flow of suspensions

Abstract: The Taylor–Couette flow of non-colloidal, neutrally buoyant spherical particle suspensions in the $\phi =0\,\%-28\,\%$ concentration range and (17–250) Reynolds number ( $\mathcal {R})$ range is studied using synchronized flow visualization and torque measurements. Both methods are applied in ramp-up/down (acceleration/deceleration of the inner cylinder) experiments to detect the various flow structure states and bifurcation natures, their critical conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 59 publications
(145 reference statements)
2
37
0
Order By: Relevance
“…As Re increased, Kang and Mirbod found that the primary transition away from CCF occurred at the same effective Re for both particle sizes, and the particles had no impact on the primary instability's critical conditions compared to pure Newtonian fluid. This behaviour conflicts with the particle-induced destabilization seen in the experimental studies discussed in the previous section [1,3,5,9]. The discrepancies between their results and the reported experimental findings were ascribed to the neglect of particle inertia and inertial migration in their simulations.…”
Section: Modelling and Linear Stability Analysismentioning
confidence: 61%
See 3 more Smart Citations
“…As Re increased, Kang and Mirbod found that the primary transition away from CCF occurred at the same effective Re for both particle sizes, and the particles had no impact on the primary instability's critical conditions compared to pure Newtonian fluid. This behaviour conflicts with the particle-induced destabilization seen in the experimental studies discussed in the previous section [1,3,5,9]. The discrepancies between their results and the reported experimental findings were ascribed to the neglect of particle inertia and inertial migration in their simulations.…”
Section: Modelling and Linear Stability Analysismentioning
confidence: 61%
“…For the TVF-WTV transition, the slope change was not distinct. Additional torque measurements were conducted by Moazzen et al [9] in a rheometer-based device. This study focused on characterizing the torque behaviour in different flow states and analysing the unsteady features of NAF structures.…”
Section: (C) Inner Cylinder Torque Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…2007); see also a recent work (Moazzen et al. 2022) on torque scaling at primary and secondary bifurcations. A preliminary analysis of our torque data at indicates that the above scaling is likely to hold beyond the secondary bifurcation at .…”
Section: Discussionmentioning
confidence: 87%